The Impact of Ageing on Diaphragm Function and Maximal Inspiratory Pressure: A Cross-Sectional Ultrasound Study - Toru Yamada; Taro Minami; Takahiro Shinohara; Shuji Ouchi; Suguru Mabuchi; Shunpei Yoshino; Ken Emoto; Kazuharu Nakagawa; Kanako Yoshimi; Mitsuko Saito; Ayane Horike; Kenji Toyoshima; et al. (Diagnostics)
Background/Objectives: The effects of ageing on the diaphragm are unclear. This study examined the association between ageing and diaphragm thickness, thickening fraction (TF), and diaphragm excursion (DE) as assessed by ultrasonography after adjusting for other factors. The relationship between these parameters and maximal inspiratory pressure (MIP) was also investigated. Methods: From 2022 to 2024, ambulatory and communicative adult volunteers and outpatients were recruited from four Japanese medical institutions. Each participant’s background factors (including height, weight, and underlying diseases) and pulmonary function test results were assessed. Diaphragm thickness, TF, and DE were evaluated using ultrasonography. Results: The study involved 230 individuals with a mean age of 55.5 years (older adults (65 years and over), n = 117; non-older adults, n = 113). In older adults, the diaphragm was thicker (2.1 vs. 1.7 mm, p < 0.001), and TF was lower (88.7% vs. 116.0%, p < 0.001), with no significant difference in DE. Multivariate linear regression analysis adjusted for sex, height, body mass index, and underlying diseases showed positive associations between age and diaphragm thickness (p = 0.001), but not with TF or DE. MIP was positively associated with DE (p < 0.001) but not with thickness or TF. Age was negatively associated with MIP, regardless of diaphragm thickness, TF, and DE (all p < 0.001). Conclusions: As the diaphragm thickens with age, neither thickness nor TF is associated with MIP; only DE is related to MIP. Additionally, ageing is negatively associated with MIP, independent of diaphragm thickness, TF, and DE. Diaphragm function should be assessed using DE rather than thickness or TF.